Ultrahigh hardness and biocompatibility of high-entropy alloy TiAlFeCoNi processed by high-pressure torsion - Edalati, Parisa; Floriano, Ricardo; Tang, Yongpeng; Mohammadi, Abbas; Pereira, Karina Danielle [UNESP]; Luchessi, Augusto Ducati [UNESP]; Edalati, Kaveh (Elsevier, 2020)
Despite significant studies on mechanical properties of high-entropy alloys (HEAs), there have been limited attempts to examine the biocompatibility of these alloys. In this study, a lattice-softened high-entropy alloy TiAlFeCoNi with ultrahigh hardness (examined by Vickers method), low elastic modulus (examined by nanoindentation) and superior activity for cell proliferation/viability/cytotoxicity (examined by MTT assay) was developed by employing imperial data and thermodynamic calculations. The designated alloy after casting was processed further by high-pressure torsion (HPT) to improve its hardness via the introduction of nanograins, dislocations and order-disorder transformation. The TiAlFeCoNi alloy with the L21-BCC crystal structure exhibited 170–580% higher hardness and 260–1020% better cellular metabolic activity compared to titanium and Ti-6Al-7Nb biomaterials, suggesting the high potential of HEAs for future biomedical applications.
Keywords: Biomaterials; CALPHAD (calculation of phase diagram) method; High-entropy alloys (HEAs); Lattice softening; Phase transformation; Severe plastic deformation (SPD)